2019
DOI: 10.1016/j.amsu.2019.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Revision of failed-posterior cruciate ligament (PCL) reconstruction due to tibial tunnel misplacement: A case report

Abstract: IntroductionPosterior cruciate ligament (PCL) reconstruction failure is a rare condition found. The failure caused by some factors, including improper graft tunnel placement. Although the proper tibial tunnel placement in PCL reconstruction is still controversial, make the tunnel placement anatomically essential to decrease the risk of failure. The use of PCL jig only to guide the direction of tibial tunnel does not always give good results.Presentation of caseWe report a case of 29 year old male with total ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The rate of revision surgery after isolated PCL-R is reported to be 3% and slightly higher (3.4%) after combined PCL-R [ 46 ]. However, only a few studies and case reports have reported on the outcomes of revision PCL-R [ 16 , 41 , 42 , 47 , 59 , 81 ]. In one study, revision PCL-R using quadriceps tendon-bone autografts in a DB technique has significantly improved patient-reported outcomes, activities of daily living, sports activity level, occupational rate, and PTT based on posterior stress radiographs in 15 patients after a mean follow-up of 44 months [ 59 ].…”
Section: Clinical Outcomes Following Pcl-rmentioning
confidence: 99%
“…The rate of revision surgery after isolated PCL-R is reported to be 3% and slightly higher (3.4%) after combined PCL-R [ 46 ]. However, only a few studies and case reports have reported on the outcomes of revision PCL-R [ 16 , 41 , 42 , 47 , 59 , 81 ]. In one study, revision PCL-R using quadriceps tendon-bone autografts in a DB technique has significantly improved patient-reported outcomes, activities of daily living, sports activity level, occupational rate, and PTT based on posterior stress radiographs in 15 patients after a mean follow-up of 44 months [ 59 ].…”
Section: Clinical Outcomes Following Pcl-rmentioning
confidence: 99%
“…Most surgeons who deal with this issue determine graft position (i.e, the tunnel where graft is situated) in tibia by measuring according to standard X-ray images: anterior-posterior and lateral projection, which is certainly not precise enough 12 , 13 , given that the results mainly depend on the morphology of bones and current position of the patient's extremities. The position of the graft can be most accurately determined from computed tomography images, especially if 3D or multiplanar reconstruction is performed 16 , 17 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Most surgeons who deal with this issue determine graft position (i.e, the tunnel where graft is situated) in tibia by measuring according to standard X-ray images: anterior-posterior and lateral projection, which certainly isnˈt precise enough 12 , 13 . The position of the graft can also be determined by analyzing images of computed tomography (CT) or magnetic resonance (MRI) along with spatial reconstruction in the knee region or by creating a specialised application that determines spatial graft position using standard X-ray images, which is the goal of this research.…”
Section: Introductionmentioning
confidence: 99%
“…Although the posterior cruciate ligament reconstruction (PCLR) technique has evolved considerably over recent decades [1,14,15], there is still no consensus regarding the optimal surgical approach for PCLR [6,11], including whether to perform single-bundle or doublebundle reconstruction [20], whether to perform transtibial or tibial inlays and the positioning of the tunnel. Currently, there are many possible reasons for the failure of PCLR surgery [21], one of which is incorrect bone tunnel placement [24], particularly positioning of the tibial bone tunnel, which is considered to be very important in PCLR [8,18].…”
Section: Introductionmentioning
confidence: 99%
“…The tibial insertion of PCL is within the posterior joint capsule adjacent to the posterior septum, popliteal artery and other neurovascular tissues, which makes drilling of the tibial tunnel during arthroscopic PCLR difficult and challenging [12,13,27]. An important reason for the failure of PCLR is that less experienced surgeons are afraid of causing damage to the posterior nerves and blood vessels, so they often place the tibial tunnel in a position anterior to the anatomic point [18]. Furthermore, controversy persists as to where the tibial tunnel is located owing to the large footprint area of the PCL insertion (160.0-220.0 mm 2 ), which is not completely covered by the current grafting method [25].…”
Section: Introductionmentioning
confidence: 99%